Biphasic targeting and cleavage furrow ingression directed by the tail of a myosin II - Fang, Xiaodong (The Rockefeller University Press, 2010)
Cytokinesis in animal and fungal cells utilizes a contractile actomyosin ring (AMR). However, how myosin II is targeted to the division site and promotes AMR assembly, and how the AMR coordinates with membrane trafficking during cytokinesis, remains poorly understood. Here we show that Myo1 is a two-headed myosin II in Saccharomyces cerevisiae, and that Myo1 localizes to the division site via two distinct targeting signals in its tail that act sequentially during the cell cycle. Before cytokinesis, Myo1 localization depends on the septin-binding protein Bni5. During cytokinesis, Myo1 localization depends on the IQGAP Iqg1. We also show that the Myo1 tail is sufficient for promoting the assembly of a “headless” AMR, which guides membrane deposition and extracellular matrix remodeling at the division site. Our study establishes a biphasic targeting mechanism for myosin II and highlights an underappreciated role of the AMR in cytokinesis beyond force generation.